Drivers of Interannual Sea Level Variability on the Northwestern European Shelf. Issue 10 (9th October 2020) - Hermans, Tim H. J.; Le Bars, Dewi; Katsman, Caroline A.; Camargo, Carolina M. L.; Gerkema, Theo; Calafat, Francisco M.; Tinker, Jonathan; Slangen, Aimée B. A.
Abstract: Sea level on the northwestern European shelf (NWES) varies substantially from year to year. Removing explained parts of interannual sea level variability from observations helps to improve estimates of long‐term sea level trends. To this end, the contributions of different drivers to interannual sea level variability need to be understood and quantified. We quantified these contributions for the entire NWES by performing sensitivity experiments with a high‐resolution configuration of the Regional Ocean Modeling System (ROMS). The lateral and atmospheric boundary conditions were derived from reanalyses. We compared our model results with satellite altimetry data and used our sensitivity experiments to show that nonlinear feedbacks cause only minor interannual sea level variability on the shelf. This indicates that our experiments can be used to separate the effects of different drivers. We find that wind dominates the variability of annual mean sea level in the southern and eastern North Sea (up to 4.7‐cm standard deviation), whereas the inverse barometer effect dominates elsewhere on the NWES (up to 1.7‐cm standard deviation). In contrast, forcing at the lateral ocean boundaries results in small and coherent variability on the shelf (0.5‐cm standard deviation). Variability driven by buoyancy fluxes ranges from 0.5‐ to 1.3‐cm standard deviation. The results of our sensitivity experiments explain the (anti)correlation between interannual sea level variability at different locations on the NWES and can be used to estimate sea level rise from observations in this region with higher accuracy. Plain Language Summary: Sea level on the continental shelf northwest of Europe is rising in the long term but is also varying strongly from year to year. This makes it difficult to determine the rate of sea level rise from observations. To improve long‐term trends computed from sea level observations, the causes of short‐term sea level variability need to be understood. Therefore, we test the influences of different components of the atmosphere and ocean on year‐to‐year sea level variability, using a numerical ocean model for northwestern Europe. We find that the varying strength and direction of winds causes large variability of sea level in the southern and eastern North Sea. In other places on the continental shelf, sea level variability is mainly influenced by the variability of atmospheric pressure. We also find that the ocean outside our model domain drives small and uniform sea level variability on the continental shelf and that there is a moderate influence of solar radiation, precipitation, and evaporation. Our results help to understand how sea level varies at different locations in northwestern Europe and to obtain better estimates of the rate of long‐term sea level rise. Key Points: We use a ROMS setup to quantify the contributions of different drivers to interannual sea level variability on the NWES for 1995–2018 Atmospheric variability is the main driver, whereas ocean variability drives small and uniform sea level variability on the shelf Wind drives large variability in the North Sea, north of the United Kingdom and around Norway, while the inverse barometer effect dominates elsewhere